Theorizing in Design Science Research - Lee, J.; Pries-Heje, J.; Baskerville, Richard (Springer-Verlag, 2011)
Theory is a central element in research. Due to the importance of theory in research, considerable efforts have been made to better understand the process of theorizing, i.e., development of a theory. A review of the literature in this area suggests that two dominant theorizing approaches are anchored to deductive and inductive reasoning respectively. In contrast, an essential part of theorizing for design may involve abductive reasoning. The purpose of design theory is not to advance declarative logic regarding truth or falseness, but to guide learning and problem solving through the conceptualization of a design artifact. This paper critically examines the process of theorizing for design by developing an idealized design theorizing framework. The framework indicates that theorizing for design operates in two distinct domains: instance and abstract. Further, four key theorizing activities are identified in this framework: abstraction, solution search, de-abstraction, and registration. The framework provides grounds for building strong design theories in the design science paradigm by explicating the underlying theorizing process for design.